Tuberculin sensitivity and HIV-1 status of patients attending a sexually transmitted diseases clinic in Lusaka, Zambia: a cross-sectional study. - Duncan, L; Elliott, A; Hayes, R; Hira, S; Tembo, G; Mumba, G; Ebrahim, S; Quigley, M; Pobee, J; McAdam, K (1995)
A cross-sectional study to estimate the prevalence of latent tuberculosis (TB) in a group of Zambians at high risk of human immunodeficiency virus type 1 (HIV-1) infection and to examine the effect of HIV-1 infection on the tuberculin response was conducted in the University Teaching Hospital in Lusaka, Zambia during July to September 1990. Patients were selected from those presenting to the out-patient clinic for first referral with either sexually transmitted or skin disease. 268 adults were included in the study; 158 (59%; 95% confidence interval [CI] = 53-65%) were HIV-1 antibody positive. Of 82 HIV-1 negative participants who returned for Mantoux skin test reading, 51 (62%; 95% CI = 57-67%) had a positive test reaction (diameter > or = 10 mm) after receiving 2 units of RT-23 tuberculin. Of 106 HIV-1 positive participants who returned, only 32 (30%; 95% CI = 26-34%) had a diameter > or = 10 mm. Nine (28%) of the HIV-1 positive and Mantoux positive participants had large reactions > or = 30 mm, compared to 4 (8%) of the HIV-1 negative, Mantoux positive participants (P = 0.03). Results in the HIV-1 negative group indicated a prevalence of latent TB of 62% in this population. HIV-1 infection was associated with a much higher frequency of negative response to tuberculin and with a few large skin test responses. Thus, in populations where HIV seropositivity is high, Mantoux skin tests cannot be used to assess those with latent TB who might benefit from chemoprophylaxis.